Digital Da’wah And Tolerance Formation: A Study Of Deddy Corbuzier’s Login Podcast on Youtube - Handayani, Annisa Dwi; Lusri Virga, Rika (Journal of Asian Wisdom and Islamic Behavior, 2025)
This study investigates how the LOGIN Season 3 program on Deddy Corbuzier’s YouTube channel fosters the internalization of religious tolerance values among university students. Rising intolerance in public and digital spaces highlights the urgency of da'wah content that promotes inclusivity. Grounded in Syukur & Hermanto’s da'wah content theory and Suyahmo’s concept of tolerance, the research employs a qualitative descriptive approach. Data were gathered through video content observation, interviews with student viewers, and analysis of audience comments. The findings show that students internalize values such as freedom of religion, interfaith brotherhood, and acceptance of diversity. This process is facilitated by the program’s casual yet substantive communication style, its use of accessible digital platforms, and its inclusive, moderate narratives. Positive engagement in the comment sections further emphasizes its effectiveness. The study concludes that LOGIN offers a contextual and impactful model of digital da'wah, enriching discourse on da'wah theory and demonstrating its potential to cultivate tolerance in a pluralistic society.